Student engagement, brand image and loyalty relationships: The mediating role of student satisfaction - Osman, Abu Rashed; Joarder, Mohd Hasanur Raihan; Hoque, Md. Kazimul; Jakowan (Journal of Education and e-Learning Research, 2024)
The aim of this study is to explore the relationship between student engagement, brand image, student satisfaction and loyalty. Furthermore, the study intends to explore the mediating role of student satisfaction in the relationship between engagement and loyalty as well as brand image and loyalty in the context of higher education. A representative sample of 296 students from the three best private universities in Dhaka has been gathered in order to test the hypotheses. The study demonstrates that brand image has a favorable impact on student satisfaction while student engagement has no influence on student satisfaction. The results show that loyalty is heavily influenced by the student satisfaction construct. When there is no mediation between student engagement and loyalty, a complete mediation is recognized when student satisfaction is a mediator between brand image and student loyalty. The study also reveals that there is a negative correlation between student engagement and satisfaction. The results of the research definitely improve brand perception which keeps students engaged to their higher education.